2019
DOI: 10.1016/j.healthplace.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Governance commitment to reduce maternal mortality. A political determinant beyond the wealth of the countries

Abstract: Some countries reached, in 2015, the Millennium Development Goal of reducing maternal mortality to 96 or less maternal deaths per 100,000 live births. Others, however, did not. This paper analyses the strength of the association between maternal mortality and each of the six components of Governance—a political determinant scarcely explored in the literature—in 174 countries. It was found that the greater the governance, the lower maternal mortality, independently of a country's wealth. We used all six indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 50 publications
1
19
0
1
Order By: Relevance
“…in those with high regulatory quality across 174 countries [9], and countries with lower scores of political stability and absence of violence were associated with higher inequality in the coverage of health interventions in the study of 80 low-and middle-income countries [10]. Using this data set of governance indicators, we found that governance is just as important as disease control measures (e.g., immunization and hygiene) in reducing a country's child mortality [11].…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…in those with high regulatory quality across 174 countries [9], and countries with lower scores of political stability and absence of violence were associated with higher inequality in the coverage of health interventions in the study of 80 low-and middle-income countries [10]. Using this data set of governance indicators, we found that governance is just as important as disease control measures (e.g., immunization and hygiene) in reducing a country's child mortality [11].…”
mentioning
confidence: 78%
“…The perception-based data were used to reflect common views regarding governance outcomes from diverse survey respondents and experts in the surveys of individuals, households, firms, commercial businesses, non-governmental organizations, and public sectors [ 6 ]. These six World Bank’s Governance Indicators have been used individually or as a whole to assess their associations with health outcomes in cross-country comparison studies, such as countries with low regulatory quality showed 12 times higher maternal mortality risk is 12 times than in those with high regulatory quality across 174 countries [ 9 ], and countries with lower scores of political stability and absence of violence were associated with higher inequality in the coverage of health interventions in the study of 80 low- and middle-income countries [ 10 ]. Using this data set of governance indicators, we found that governance is just as important as disease control measures (e.g., immunization and hygiene) in reducing a country’s child mortality [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, on the contrary in countries with weak accounting and government practices tend to have ineffective and weak monitoring mechanisms [1,4,6] thereby causing monitoring and information costs to be inefficient [21,60]. In these countries it is likely that violations from powerful officials cannot be punished, frauds can be covered up through manipulation of records and most likely independent oversight institutions are entangled in corruption networks (Changwony and Paterson [24], Paterson et al [26], Ruiz-Cantero, Guijarro-Garvi, Bean, Martínez-Riera, and Fernández-Sáez [72]). Therefore, monitoring mechanisms will not work effectively in countries with weak quality accounting practices [3,50,56], so economic growth is hampered [12,18,55] Overall, all of the above statements show that high-quality accounting practices will weaken the relationship of corruption to economic growth and vice versa low-quality accounting practices will strengthen the relationship of corruption to economic growth.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In addition, women with social disadvantages experience difficulties in daily life, usually have more focus on livelihood support than healthcare; they have inequitable distribution of livelihood opportunities and resources that contribute to poor access to and higher discontinuation of routine MNH visits. These factors are mostly non-modifiable and often require long term sociopolitical interventions [45][46][47][48], and technical and biomedical focussed approaches on their own may not improve MNH visits across the CoC [47]. Longer-term structural interventions to improve MNH CoC may include improving female access to formal and informal education and employment opportunities [45].…”
Section: Discussionmentioning
confidence: 99%